Expanded Access to Naloxone Among Firefighters, Police Officers, and Emergency Medical Technicians in Massachusetts - Davis, Corey S. (American Public Health Association, 2014)
Naloxone is a medication that reverses respiratory depression from opioid overdose if given in time. Paramedics routinely administer naloxone to opioid overdose victims in the prehospital setting, and many states are moving to increase access to the medication. Several jurisdictions have expanded naloxone administration authority to nonparamedic first responders, and others are considering that step. We report here on policy change in Massachusetts, where several communities have equipped emergency medical technicians, law enforcement officers, and firefighters with naloxone.